The effect of binder molecular weight and talc mineral filler on expansion ratio and hardness in intumescent material. (3rd November 2022) - Tu, Nguyen Thi Ngoc; Van Duan, Le; Trang, Tran Thu; Lien, Nguyen Thi; Ninh, Vu The; Ly, Giang Thi Phuong; Dung, Nguyen Viet
Abstract: Intumescent flame retardant coatings were prepared including binder (acrylic resin), solvent, TiO2, talc and flame retardant system (ammonium polyphosphate‐APP, pentaerythritol‐PEN, and melamine‐MEL). To evaluate the effect of molecular weight on the swelling process as well as the hardness of the charred layer, the acrylic resins with different molecular weights were applied. In particular, by incorporating of talc mineral, the performance of the APP‐PEN‐MEL system is significantly improved. The results showed that the highest molecular weight acrylic resin has the best expansion ratio (53.72 times) and the highest hardness of charred layer (15.5 N at the compression of 30 %). The coating with 2.5 % talc powder can be considered as an optimized content of the char layer. Abstract :